'What is going on here?' Gazing, Knowledge and the Body at a Pilgrimage Shrine. Issue 1 (1st June 2020) - Eade, John
Abstract: This article focuses primarily on the role of the camera in representing the famous, much visited Roman Catholic shrine of Lourdes, France, and what this role tells us about the relationship between gazing, knowledge, and the body. After outlining the historical development of the shrine, the discussion proceeds to consider the growth of popular media and the cinematic gaze, the expansion of tourism, debates concerning the morality of gazing at bodies as personal cameras and smartphones becoming increasingly available and used at the shrine, the representation of human and saintly bodies, and the part played by the camera in the attempt to ensure security.